Digital Competence, Learning Innovation, and Work Motivation as Determinants of Teachers’ Performance - Nasrul Elmi; Saiful Bahri; Hera Yanti (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
Teacher performance is a crucial factor influencing educational quality, especially throughout digital transformation and pedagogical progress. This study, based on human capital theory, innovation diffusion theory, and motivational psychology, examines the impact of digital competence, learning innovation, and work motivation on the performance of junior high school teachers in Aceh Tamiang Regency, Indonesia. A quantitative explanatory design was utilized, employing 210 teachers chosen by proportional random selection. Data were gathered utilizing validated questionnaires and examined by path analysis. The findings indicate that digital competence, learning innovation, and job motivation each exert a substantial beneficial influence on instructors' performance (p < 0.05). Of these variables, work motivation exhibits the most significant direct impact, succeeded by digital competence and learning innovation. The concurrent analysis reveals that the three predictors collectively account for a significant percentage of the variance in teachers' performance, hence validating the strength of the proposed conceptual framework. These findings underscore the significance of a cohesive teacher development strategy that enhances technology proficiency, fosters educational creativity, and maintains motivational support. The study enhances the literature on educational effectiveness by presenting an empirically based model of teacher performance that encapsulates the integrated roles of competence, creativity, and motivation in the context of educational digitalization.